Authentic Leadership and Innovative Work Behaviour: Exploring the Role of Trust, Power Distance Orientation, and Job Satisfaction - Lewicka, Dagmara; Rehman, Hafeez Ur (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: In today’s rapidly evolving business landscape, the role of authentic leadership in fostering innovative work behaviour among employees has gained significant attention. This paper explores and analyses authentic leadership’s influence on innovative work behaviour. Furthermore, it examines the mediation role of trust in leaders and the moderation role of power distance orientation and job satisfaction within this relationship.Research Design & Methods: A systematic literature review was conducted to identify relevant studies on authentic leadership, innovative work behaviour, trust, power distance orientation, job satisfaction, and their interrelationships. The selected studies were critically analysed to identify common themes, methodologies, and findings. We employed the PRISMA method to choose the papers and bibliometric analysis was performed through VOS viewer software.Findings: We provide insights into how authentic leadership influences employees’ innovative work behaviour by examining relevant literature. This paper also provides research gaps based on existing literature and empirical research. The review integrates and analyses existing literature to provide insights into the relationships between the variables.Implications / Recommendations: Organisations should prioritise developing authentic leaders who build trust and create a supportive environment for innovation. Fostering a culture of low power distance and employee involvement enhances the positive impact of authentic leadership on innovation. Additionally, improving job satisfaction through various strategies promotes an innovative work environment.Contribution: As far as we know, prior studies have not investigated how job satisfaction and power distance orientation influence the connection between authentic leadership and innovative work behaviour. This paper contributes to the literature by providing insights into the intervening roles of job satisfaction and power distance orientation in the unique context of Pakistani start-ups.